Comparison of the effects of varying tube voltage and iodinated concentration on increasing the iodinated radiation dose in computed tomography. (March 2022) - Hoshika, Minori; Nakaura, Takeshi; Oda, Seitaro; Kidoh, Masafumi; Nagayama, Yasunori; Sakabe, Daisuke; Hirai, Toshinori; Funama, Yoshinori
Highlights: Iodinated radiation dose was more pronounced with increasing iodine concentrations. Iodinated radiation dose was higher in the peripheral portion than center portion. Iodinated radiation dose for 80 kV was slightly increased that for 120 kV. Abstract: Purpose: To compare the effects of tube voltage and iodinated concentration on increasing the iodinated radiation dose in computed tomography (CT). Material and methods: Water and iodinated materials were inserted in an anthropomorphic thorax phantom. Helical CT scans were performed with tube voltages of 80 and 120 kV. Monte Carlo simulation of radiation doses in CT images was used to study the radiation dose profiles. The radiation doses at different iodine to water ratios in images were calculated from cumulative radiation doses for iodine and water at each iodine concentration, tube voltage, and peripheral/central location. A radiation dose ratio from 80 to 120 kV was calculated from cumulative radiation doses at the same iodine concentration. Results: The iodinated radiation doses with small and large phantoms were 1.56–2.04 and 1.61–1.82 times higher at 80 kV and 1.55–2.23 and 1.22–1.79 times higher at 120 kV than those in water. In the central portion, the iodinated radiation dose ratio decreased by 1.14–0.75 and 1.20–0.93 times at 80 kV and 1.29–1.23 and 1.17–1.23 times at 120 kV with increasing iodinated concentrations. In the peripheral portion, the iodinated radiation dose was slightly higher for 80 kV than for 120 kV. In the central portion, the ratio decreased with increasing iodinated concentration. Conclusion: The increase in iodinated radiation dose caused by photoelectric absorption was greater with increased iodine load than with lower tube voltage.